1997
DOI: 10.1097/00000658-199707000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Resection Combined With Intraoperative Radiation Therapy for Pancreatic Cancer

Abstract: ObjectiveThe objective of the study was to analyze a single center's experience in the treatment of pancreatic carcinoma with a combination of pancreatic resection and intraoperative radiation therapy (IORT). Summary Background DataPancreatic cancer is the most lethal form of gastrointestinal malignancy. Historically, it carries a 20% 1-year survival and a 5-year survival of 3% to 5%. Since 1987, patients at Thomas Jefferson University Hospital have been offered IORT in an attempt to improve their survival. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 10 publications
0
34
0
3
Order By: Relevance
“…Owing to the highly aggressive invasion, early metastasis and nonspecific symptoms characteristic of this malignancy, 90% of patients are diagnosed with surgically unresectable disease (Farrell et al, 1997). Current chemotherapy regimes offer only marginal survival benefit, and alternative therapeutic strategies are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the highly aggressive invasion, early metastasis and nonspecific symptoms characteristic of this malignancy, 90% of patients are diagnosed with surgically unresectable disease (Farrell et al, 1997). Current chemotherapy regimes offer only marginal survival benefit, and alternative therapeutic strategies are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic adenocarcinoma is characterized by aggressive invasion and early metastasis, such that 90% of patients have surgically unresectable advanced disease at the time of diagnosis. Even patients without overtly advanced disease often subsequently develop metastases and tumor recurrence despite apparently curative resection (Farrell et al, 1997). Anoikis resistance represents a potential target for novel antimetastatic strategies directed at preventing or slowing progression of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…31 Importantly, the addition of IORT after PD did not increase perioperative complication rates significantly in the current series, which is consistent with the earlier experience from our institution. 22 Although late complications have been reported after IORT for pancreatic cancer, our results and other reports suggest that IORT may be delivered safely in combination with surgical resection. 24,26,28,32,[33][34][35][36][37] Selection of 38,39 These studies created a foundation for the rational delivery of IORT in humans, so it should not be surprising that clinical studies have shown these RT doses to be safe and feasible.…”
Section: Adjuvant Ebrt (N=75)mentioning
confidence: 39%
“…Prior reports from our institution have described outcomes of patients who received IORT for resectable and unresectable pancreatic cancer prior to 1995. 13,22 The current study evaluates outcomes for patients who received treatment for resectable pancreatic cancer from 1995 to 2005. As a result of physician bias for the use of IORT in more advancedstage pancreatic cancer at our institution, it was not possible to identify a comparative group of patients for use in a matched pair analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation